2017
DOI: 10.1002/jssc.201700579
|View full text |Cite
|
Sign up to set email alerts
|

Fast analysis of quaternary ammonium pesticides in food and beverages using cation‐exchange chromatography coupled with isotope‐dilution high‐resolution mass spectrometry

Abstract: A fast separation based on cation-exchange liquid chromatography coupled with high-resolution mass spectrometry is proposed for simultaneous determination of chlormequat, difenzoquat, diquat, mepiquat and paraquat in several food and beverage commodities. Solid samples were extracted using a mixture of water/methanol/formic acid (69.6:30:0.4, v/v/v), while liquid samples were ten times diluted with the same solution. Separation was carried out on an experimental length-modified IonPac CS17 column (2 × 15 mm ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Although sugar appears as a strong driver of the association, other chemical compounds might also play a role, such as 4-methylimidazole, an additive in drinks that contain caramel colouring (eg, sodas) or pesticides that might be associated with increased risk of cancer and could be present in fruit juice 1918 20 75 Regarding 100% fruit juices, one other explanation could be that fruit juice antioxidants might interact with tobacco smoke to potentialise carcinogenesis 51.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sugar appears as a strong driver of the association, other chemical compounds might also play a role, such as 4-methylimidazole, an additive in drinks that contain caramel colouring (eg, sodas) or pesticides that might be associated with increased risk of cancer and could be present in fruit juice 1918 20 75 Regarding 100% fruit juices, one other explanation could be that fruit juice antioxidants might interact with tobacco smoke to potentialise carcinogenesis 51.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the obesity and adiposity pathways, mechanisms underlying a link between sugary drinks and cancer might involve insulin resistance caused by their high glycaemic index or glycaemic load, which have been related to breast cancer,13 14 hepatocellular cancer,15 and diabetes related carcinomas 16. The chemical compounds in sugary drinks, such as 4-methylimidazole in drinks containing caramel colourings (defined as possibly carcinogenic to humans by the International Agency for Research on Cancer, IARC),17 18 pesticides in fruit juices,19 20 or artificial sweeteners such as aspartame might play a role in carcinogenesis 21…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the literature report levels of 1 (and mepiquat) in the selection of processed foods. They show that 1 is detected in bread samples of different cereal compositions in the range 50–200 μg/kg ( n = 292, 41% with 1 detected) or 10–130 μg/kg ( n = 3, 100% 1 detected), as well as in orange and apple juices at 125 ng/L ( n = 5, 20% 1 detected) and 7100 ng/L ( n = 1, 100% 1 detected), respectively. 1 was also found in cereal snack bars ( n = 96, 64% 1 detected) and breakfast cereals ( n = 144, 25% 1 detected), and it was observed that products containing either oat or wheat bran did contain 1 predominantly .…”
Section: Resultsmentioning
confidence: 99%
“…These findings also give a hint that distinguishing cloudy juice from clear juice in further studies will help to better access the intrinsic effects of different types of juice. Although the nutrients appear as the main driver of the association, other chemical compounds, such as pesticides or additives in the bottled fruit juice products, might also be causal factors [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%